Empirical Study Concerning Industrial Services within the Austrian Machinery and Plant Engineering Industry - Matyas, K.; Rosteck, A.; Sihn, W. (Cranfield University Press, 2009)
Industrial Services adapted to the requirements of the customers and aligned with the specifications of the physical products are becoming increasingly important for companies in the engineering industry in order to remain competitive and to ensure long-term economic success. An empirical study in the Austrian machinery and plant engineering industry should systematically evaluate and document corporate practice with regard to services. The current service landscapes in companies and the development of customer requirements have been investigated. The result of the study is a general idea of what the future needs for action in these companies as well as in applied research are.
Organised by: Cranfield University
Keywords: Industrial Services; Engineering Industry; Service Development; Service Management